Effect of rayleigh number on internal eccentricity in a heated horizontal elliptical cylinder to its coaxial square enclosure - Bouras, Abdelkrim; Taloub, Djedid; Driss, Zied (Zielona Góra: Uniwersytet Zielonogórski)
This paper deals with numerical investigation of a natural convective flow in a horizontal annular space between a heated square inner cylinder and a cold elliptical outer cylinder with a Newtonian fluid. Uniform temperatures are imposed along walls of the enclosure. The governing equations of the problem were solved numerically by the commercial code Fluent, based on the finite volume method and the Boussinesq approximation.
Keywords: natural convection; Newtonian fluid; geometry ratio; Rayleigh number; elliptical cylinder